Shifts of Place In Abdul-Rahman Munif's Narratives Between the Original & the Loan The Novel Cities of Salt: an Archetype - Marroushyieh, Muhammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The presence of place in Abdul-Rahman Munif's Narratives is one of the principal characteristics of the modern Arabic Novel. We do not exaggerate to claim that the place has changed into a central character in his prosaic works, because it represents the primordial space to all prosaic components, and it stands as the cradle of all human existence, since it enjoys the possibility of transformation and summarizing concepts. Part of the problem that this piece of research endeavours to disclose depends on explaining the magnificent turbulances of place as a result of the human conduct which does not consider the ethical and human issues quite remarkably since it aims at achieving its totalitarian and materialistic interests at every cost. The great shifts of place in the novel Cities of Salt emerge as the outcome of the destructive human behaviour toward the virgin nature (intrinsically and extrinsically), where Munif concurrently struggles to uncover the underlying psychological, sociological, political and economic consequences that the human being of the Arab Peninsula has been exposed to. At the same time, we conclude that the place has also left observable impacts on mankind; henceforward, man starts complaining from alienation, disorientation and loss of identity owing to the grand shifts manifested by the place.